Elevation Technique for Medial Branch based Superficial Circumflex Iliac Artery Perforator flap - Suh, Young Chul; Hong, Joon Pio; Suh, Hyunsuk Peter (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
According to early studies on the superficial circumflex iliac artery perforator flap, there are two major types of perforators that are presumed to originate from the superficial circumflex iliac artery: the medial perforator with a direct cutaneous vessel (superficial branch) - located relatively medially on the flap, and the lateral perforator, traveling laterally beneath the deep fascia and often with an intramuscular pathway penetrating the deep fascia on the lateral aspect (deep branch) of the flap. Although there are well described studies on the anatomy of the arterial vasculature, design and elevation of the flap are different issues, as there are always some potential for anatomical variations, such as pedicle anatomy, location of lymph nodes, and thickness of superficial fascia. The presence of internal pudendal artery and superficial inferior epigastric artery in the groin may add to the confusion. One should also beware of the presence of major lymphatics which are drained into the superficial venous system. Therefore this paper will try to simplify the elevation technique based on the medial perforator. However, one must always be ready to identify a good perforator and to elevate it as a freestyle approach to overcome the variations wherever the perforator may originate from. The best way to feel comfortable using any flap is from practice and repetitive elevation. The same is for the medial branch based SCIP flap. The direct cutaneous nature of the pedicle will make the dissection even easier as the dissection course bypasses muscle and lymph nodes. This technical note describes practical surgical tips for elevating the medial perforator based SCIP flap.
Keywords: Flap elevation; SCIP; color doppler; microsurgery